Self-Learning Cooking Application - Shaharuddin, Syafiqah Elma; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2021)
Self-learning cooking application is an application that provide a self-taught guide on cooking for its users. The idea to implement this project are triggered where the people are depending on printed or online book to cook, difficulty to estimate cooking time, inaccuracy to estimate amount of groceries and calculate calories for the food taken. Thus, the objective of this project are to design the self-learning cooking application using Android Studio, to develop the self-learning cooking application using Android Studio and to test the functionality of the application. An interview session was conducted to gather the requirements from the expertise which are chef, influencer and dietitian. They recommend to build an application for the self-learning cooking with a help from the expertise such as design, recipes, and a lot more ideas. This system is driven by activities in prototyping model. Android Studio software will be use to code and Firebase as software database. This application provides features such as making own cooking schedule, display the list of groceries and total amount of calories from chosen recipes. The result shown that the test cases is 100% pass. Moreover, this application is free and is suitable for adult menu. As the conclusion, hopefully this application can help people to cook effectively.